Phonemic Correspondences between Bahasa Indonesia and Sinama - Roxanne Marie Flores; Hendrokumoro (Universitas Islam Negeri Palopo, 2026)
This study identifies systematic phonemic correspondences between Bahasa Indonesia and Sinama through a comparative phonemic analysis using the 200-item Swadesh list as the data basis. Data were obtained from officially published dictionaries, and in the case of Sinama, consultations with a native speaker. Cognate pairs were identified by cross-referencing the gathered data with Proto-Austronesian (PAN) reconstructions. Results show that Sinama yields a remarkably high lexicostatistical similarity with Bahasa Indonesia with 43.89% cognacy, putting Bahasa Indonesia and Sinama in the level of language family subgrouping. Six systematic phonemic correspondences were identified between the two languages: elision of /h/ in initial and final word positions, the raising of /a/ to /o/ before final /m/, multiple changes on the vowel /e/, correspondences on /r/, and the lateralization of /j/ to /l/. In addition, twenty-six cognate pairs were found to be completely identical between the two languages. These results show the shared Austronesian heritage between Bahasa Indonesia and Sinama and the distinct phonological developments each language has undergone over time. This study also shows the importance of including understudied regional languages, such as Sinama, in comparative linguistics research on Indonesian and Philippine languages.